The Relationship between Total Blood Cholesterol Level and VO2 max in 6-Minute Walk Test An Analitical Observational Study in Students of Medical Faculty UNISSULA aged 19 to 21 years - Innash, Rahmaan; Rosdiana, Ika (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2013)
The increase in total cholesterol level is a risk factor for coronary heart diseases leading to decrease in fitness. VO2 max is the biggest advocate for heart and lung fitness. There have been few studies conducted on relationship between total cholesterol level and VO2 max. The purpose of the study was to determine the relationship between total colesterol level and VO2 max through the 6-minute walk test. In this Analytical observational study with the population of medical faculty students of 2009, 2010, 2011 included 51 persons aged 19-21 years. Total cholesterol level was measured by specthrophotometer from blood. VO2 max analyzed by the 6-minute walk test. The study resulted in mean VO2 max of 24.48 ml/kg/min, mean of total blood cholesterol of 164.16 mg/dl. Pearson correlation test showed there was a significant correlation between total blood cholesterol level and VO2 max (p < 0.05), with negative correlation r = -0.281. An increase in the blood levels of total cholesterol will decrease physical fitness (VO2 max).